Pendampingan Penyusunan Laporan Keuangan pada BUMDES Tatondong Desa Popareng - Wenny Anggeresia Ginting; Jerry Sonny Lintong; Ivoletti Merlina Walukow; Estrelita V.Y Waney; Olivia V. Lendeng; Debora J. M Posumah (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Negeri Manado, 2022)
BUMDes as an economic institution that is fully managed by village communities is obliged to present SAK ETAP-based financial reports. This is a form of accountability for BUMDes management in managing finances. Through financial reports, the performance of BUMDes management related to financial management can be evaluated. BUMDes financial reports demonstrate the professionalism, transparency, accountability and reputation of BUMDes to other parties with an interest in BUMDes operations. Because many BUMDes administrators do not understand, it is necessary to have technical instructions for preparing BUMDes financial reports. Community Service Activities (PKM) at BUMDes Tatondong, Popareng Village, Tatapaan District, South Minahasa Regency, aims to assist in preparing SAK ETAP-based BUMDes financial reports in order to improve the quality of their performance. The data analysis technique in this research is the participatory discussion method which is carried out in the field. Based on the results of the study, it was shown that the recording (journal) of various transactions carried out in the classification of transactions at BUMDes Tatondong was not in accordance with SAK ETAP. BUMDes Tatondong presents financial reports in only two types, namely balance sheets and income statements, while according to SAK ETAP there are five types, namely balance sheets, income statements, statements of changes in equity, cash flow statements, and notes to financial statements.